Association of objectively measured lifting load with low-back pain, stress, and fatigue: A prospective cohort study - Rúni Bláfoss; Per Aagaard; Thomas Clausen; Lars L Andersen (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVES: Limited knowledge exists about the association of lifting loads on a daily basis with physical and mental symptoms among warehouse workers. This study investigated associations between objectively measured lifting load and low-back pain (LBP), mental stress, and bodily fatigue after work and the following morning. METHODS: Warehouse workers (N=85) from the retail industry replied to daily questionnaires before and after work for 21 days about LBP intensity, mental stress, and bodily fatigue (outcome, all scales 0-10). We assessed lifting exposure using company records from the warehouse logistic systems on total lifting load (kg) per workday. Associations between variables were tested using linear mixed models with repeated measures controlling for relevant confounders. RESULTS: Mean daily lifting load was 1667.2 kg (range: 0-9998.4 kg). Compared to lifting 0-499 kg during a workday, lifting 500-1999 kg was associated with 0.59 points [95% confidence interval (CI) 0.10-1.08] elevated LBP intensity after work, while lifting ≥5000 showed a higher LBP intensity of 1.26 points (95% CI 0.48-2.03). LBP intensity remained elevated the following morning. Lifting ≥5000 kg was associated with higher mental stress after work of 0.74 points (95% CI 0.10-1.37), while no association was observed for bodily fatigue. CONCLUSIONS: Higher daily lifting loads were associated with higher LBP intensity after work and the following morning. These findings suggest that warehouses should consider the daily lifting loads when organizing warehouse work to prevent development of LBP, eg, using company records to provide a more equal distribution of daily lifting loads between workers.